Recent development of hydrothermal liquefaction for algal biorefinery. (April 2020) - Gu, X.; Martinez-Fernandez, J.S.; Pang, N.; Fu, X.; Chen, S.
Abstract: Hydrothermal liquefaction (HTL) is considered as one of the most promising methods for converting algal biomass to bio-oil and other value-added chemicals. The conventional HTL process, however, is limited by its incapability of recovering high-value bioactive compounds that are desirable for enhancing overall process feasibility. The two-stage sequential hydrothermal liquefaction (SEQHTL) process was proposed as an alternative to overcome this limitation. SEQHTL operates at reduced temperature and pressure to facilitate production of co-products in addition to bio-oil. This article offers a comprehensive review of the SEQHTL process in comparison with conventional HTL. Main topics include: operation principles and targeting final products of HTL, reaction mechanisms of algal biomass in the HTL process, recent publications on algae-related HTL studies, features of the SEQHTL process, advantages of the SEQHTL process for production of high quality bio-oil as well as extraction of prospective high-value co-products that may be harvested from microalgae biomass, cost advantage of the SEQHTL process, challenges identified with techno-economic and life-cycle assessments, and suggested future HTL research and development in comparison with other conversion technologies. All these aspects collectively provide an overview of the SEQHTL technology. Graphical abstract: Image 1 Highlights: Performance of two-stage hydrothermal liquefaction process is critically reviewed. Two-stage process enables co-product recovery along with algal bio-oil production. Two-stage process leads to lower cost due to the reduced operating temperature. Different algal conversion technologies are compared. Challenges and development of algal hydrothermal liquefaction process are evaluated.